DIAGNOSTICS OF BONE METABOLISM DISORDERS IN ONCOLOGICAL DISEASES - O. I. Apolikhin; B. Y. Alekseev; A. V. Sivkov; N. G. Keshishev; A. A. Trudov; E. Z. Rabinovich; A. A. Kachmazov (Исследования и практика в медицине)
Osteoporosis is one of the most significant bone complications of cancer. About 1.5 million cancer patients worldwide have bone metastases. Patients with myeloma, breast cancer, prostate, thyroid, bladder and lung have very high risk of development of bone lesions and related complications. Currently, osteodensitometry is the gold standard for the diagnosis of osteoporosis. In recent years we frequently use the innovative imaging techniques for bone metastases, such as CT, MRI, PET/CT. Unfortunately, the diagnostic value of these methods is that it is not always possible to identify abnormalities of bone metabolism in cancer, especially in the early stages. This review shows the world experience of usage of biochemical markers of bone resorption (calcium, hydroxyproline, NTX, CTX, PYD, DPD, TRAP-5b, bone sialoprotein - BSP) and markers of bone synthesis (osteocalcin, CSF, ACF, Karlovy vary IFF), their advantages and disadvantages. The level of these markers is increased in most patients with osteoporosis and bone metastases, it is suggesting a potential role in early diagnosis of bone metastases.